The Complex Torque Coefficient Applied in Subsynchronous Oscillation Caused by HVDC. (May 2019) - Zhang, Hanhua; Li, Jiaqi; Wen, Jun; Zhang, Shuang; Tian, Bei
Abstract: Subsynchronous oscillation is an unstable state in power system, which may damage rotors of turbine generators and break the steady operation of the power system. In China, some accidents of subsynchronous oscillations had happened in the power stations where there are HVDC projects nearby. So that it is necessary to study the Subsynchronous oscillation caused by HVDC. After analysis of the principle of subsynchronous oscillation, the mathematical calculation model of the system containing HVDC is built and analysed in method of complex torque coefficient. And the simulation model is established in PSCAD/EMTDC to prove the validation of the method of complex torque coefficient used for the system containing HVDC, which combines calculation and simulation of the method for the system.